Grouping of export commodity flows by direction of change - Malyarenko, O. V. (My University, 2021)
There are real prospects for the creation of a truly open economy in our country. Active use of foreign economic factors contributes to overcoming the negative processes in the economy and further development of market relations. Ukraine's export potential is determined by the volume of goods and ambassadors that can be produced in the economic and social spheres and can be sold on the world market with the maximum benefit for the country. The main purpose of this article is to analyze statistical data and study the peculiarities of changes in export flows of Ukraine.
Keywords: economy; market relations; export flows